2014
DOI: 10.3892/or.2014.3560
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of plasma HGF level for monitoring acquired resistance to EGFR tyrosine kinase inhibitors in non-small cell lung cancer

Abstract: Monitoring of molecular markers is indispensable for deciding subsequent treatment after acquired resistance to molecular-targeted therapy. According to results using re-biopsy, EGFR T790M mutation and overexpression of hepatocyte growth factor (HGF) are major mechanisms of acquired resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs). The aim of the present study was to assess whether quantification of HGF using peripheral blood in addition to detection of T790M with plasma DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…In addition, the expression levels of EGFR, HER2 and HER3 were determined in primary tumors of colorectal cancer cells, and corresponded with lymph node metastases and liver metastases (42,43). The dysregulation of human EGFR pathways by the overexpression or constitutive activation promote s tumor processes, angiogenesis and metastasis in several types of human cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Previous studies have demonstrated that tetrandrine inhibits cell metastasis in 4T1 breast cancer cells (18) and CT26 colorectal cancer cells in vivo (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the expression levels of EGFR, HER2 and HER3 were determined in primary tumors of colorectal cancer cells, and corresponded with lymph node metastases and liver metastases (42,43). The dysregulation of human EGFR pathways by the overexpression or constitutive activation promote s tumor processes, angiogenesis and metastasis in several types of human cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Previous studies have demonstrated that tetrandrine inhibits cell metastasis in 4T1 breast cancer cells (18) and CT26 colorectal cancer cells in vivo (25).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal protein activity and/or expression levels of EGFR have been correlated with the etiology of several types of human cancer, including colorectal cancer (4,5), non-small cell lung cancer (6,7), breast cancer (8,9), head and neck squamous cell carcinoma (10,11), pancreatic cancer (12) and brain cancer (13). EGFR-targeted therapy has been validated in human colorectal cancer (14), and the chemotherapeutics include pharmacological agents, including cetuximab (Erbitux), which is an EGFR inhibitor (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the system utilizes peripheral blood, it is possible to examine T790M repeatedly. Our previous retrospective study using the MBP-QP system demonstrated that T790M was detected in 53-56% of patients who acquired resistance to EGFR-TKI (28,29). In addition, a prospective multicenter observational study was then performed to determine whether T790M detection using MBP-QP system with plasma DNA was useful for monitoring acquired resistance to EGFR-TKI, and T790M was reproducibly detected in 40% of patients whose disease became progressive (30).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a prospective multicenter observational study was then performed to determine whether T790M detection using MBP-QP system with plasma DNA was useful for monitoring acquired resistance to EGFR-TKI, and T790M was reproducibly detected in 40% of patients whose disease became progressive (30). HGF levels in the plasma were also determined, and an elevation of HGF of ≥1.5-fold was observed in 38% of the population (29). A combination of T790M detection and HGF quantification using plasma revealed that T790M and/or elevation of HGF were detected in 69% of that population.…”
Section: Introductionmentioning
confidence: 99%